Correction: Ji et al. The Impact of Bilirubin on 7α- and 7β-Hydroxysteroid Dehydrogenases: Spectra and Docking Analysis. Catalysts 2023, 13, 965 - Ji, Qingzhi; Chen, Jiamin; Zhu, Luping; Wang, Ruiyao; Wang, Bochu (Catalysts, 2025)
Following publication, concerns were raised regarding the peer-review process related to the publication of this article [...]